Design and development of MR damper for two wheeler application and Kwok model parameters tuning for designed damper. (June 2022) - Devikiran, Pinjala; Puneet, NP; Hegale, Abhinandan; Kumar, Hemantha
Magnetorheological dampers have been the interest of many researchers for a few decades for the reason of being an effective and rapidly progressing technology in the field of semi-active controlled suspension. The dynamic behaviour of these devices with nonlinear hysteresis is quite a complicated phenomenon. Hence, this paper aims at the design, modelling and simulation of a custom-made MR damper for a two-wheeler vehicle. The Kwok model has been chosen to mathematically model the MR damper. The model parameters have been optimised by minimizing the error difference between experimental and model-generated force results. A PID control is designed to control the damper effectively depending on the deflection of the damper. The two-wheeler vehicle modelled with four degrees of freedom is coupled with a mathematical model of MR damper in front and rear suspension. Further, the dynamic analysis has been performed in MATLAB/Simulink considering random road input for different velocities and current input conditions. The improved performance of MR damper was observed in suppressing road irregularities using a PID controller. As an implementation part of the work, the developed damper has been implemented in a two wheeler vehicle for performance evaluation at on-road testing conditions. The results showed significant improvement in damper performance with increment of constant current controlling MR dampers.